2013
DOI: 10.1089/tmj.2012.0306
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance of e-Health Solutions Among Patients with Chronic Respiratory Conditions

Abstract: Objective: The main objective of this study was to assess the acceptance of the use of e-health applications by patients suffering from bronchial asthma and other chronic respiratory conditions. Subjects and Methods: The questionnaire, consisting of 73 items, was distributed among 200 patients remaining under the care of a tertiary-care pulmonology center in Krakow, Poland (return rate, 82.5%; n = 165). Results: The mean age (standard deviation) of respondents was 50.8 (14.9) years. Of the respondents, 48.5% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
35
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 50 publications
9
35
1
2
Order By: Relevance
“…Moreover, it was observed that in both study groups the respondents searched for health-related information online, even though they declared that health-related information published on the Internet is not credible in their opinion. Similar results were obtained by Duplaga [16]; in a study carried out in Poland in a group of 165 patients suffering from asthma, chronic obstructive pulmonary disease (COPD) or other diseases of the respiratory system. It is worth underlining that only 16.7% of respondents in the study by Duplaga searched for information on how other patients coped with a similar health issue [16].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, it was observed that in both study groups the respondents searched for health-related information online, even though they declared that health-related information published on the Internet is not credible in their opinion. Similar results were obtained by Duplaga [16]; in a study carried out in Poland in a group of 165 patients suffering from asthma, chronic obstructive pulmonary disease (COPD) or other diseases of the respiratory system. It is worth underlining that only 16.7% of respondents in the study by Duplaga searched for information on how other patients coped with a similar health issue [16].…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were obtained by Duplaga [16]; in a study carried out in Poland in a group of 165 patients suffering from asthma, chronic obstructive pulmonary disease (COPD) or other diseases of the respiratory system. It is worth underlining that only 16.7% of respondents in the study by Duplaga searched for information on how other patients coped with a similar health issue [16]. In the present study this percentage was considerably higher -it amounted to 33%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Educating patients with regard to COPD is crucial for better disease management, greater treatment adherence, better symptom control, and consequently, better quality of life. 17 The aim of this study was to assess the proportion of subjects with COPD in São Paulo who access the internet for information about their disease. Only 13.9% of the 382 subjects with COPD who were interviewed used the internet to search for information about their disease, and this access was directly related to high economic level (including education level), low-grade dyspnea, and having a computer at home.…”
Section: Discussionmentioning
confidence: 99%
“…Со-гласно статистике ВОЗ, число людей, имеющих хотя бы одно хроническое заболевание, неуклонно возрастает и составляет до 40 % от общей численности населения [21]. Как отмечают эксперты, эффективность их лечения зависит от регулярности взаимодействия врача и пациента, что требует значительных расходов в рамках системы здравоохранения.…”
unclassified